A comparative study of short-term post caesarean section complications in normal versus gestational diabetic mothers - Hossain, M. Muktar; Rahman, Sadia; Sufian, M. Mir; Islam, M. Saiful; Gaffar, M. Abu Jar; Ahmed, Mirza Shakil (International Surgery Journal, 2023)
Background: There are variegated complications following caesarean section that may compel the mothers to stay longer in hospital with sufferings or to carry a long period of morbidity at home. Unfortunately, these complications are more in gestational diabetes mellitus (GDM). This study was designed to compare post-operative complications following caesarean sections in normal and GDM Mothers. Methods: This study was conducted in the Department of Obstetrics and Gynecology, 250 bedded general hospital, Naogaon, Bangladesh, from January 2022 to June 2023. In this study 74 participants were included consecutively. Among these, 37 mothers had GDM and 37 had normal pregnancies as control. After caesarean section, data regarding sociodemographic, obstetric and surgical profile were recorded and analyzed. Results: The mean age of the participants in GDM group was 31.32±5.56 years and in normal pregnant group was 29.24±5.56 years. Post-operative pain were almost same in both groups. Mean time of PO mobilization was 25.2 hours in GDM group and 20.2 hours in normal group. 16 patients in GDM group had PO complications and 6 in normal mothers. Among the complications SSI and UTI were more common in GDM group. No mortality was recorded. Average hospital stay were 5.9 days and 4.9 days in GDM and normal patients. Conclusions: Some post-operative complications are more common in GDM mothers. So, good glycemic control, appropriate surgical technique and proper post-operative care are needed to reduce post-operative morbidity and hospital stay.